2018
DOI: 10.1115/1.4039555
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation-Driven Defect Generation in Thick Composite Parts

Abstract: Fiber waviness is one of the most significant defects that occurs in composites due to the severe knockdown in mechanical properties that it causes. This paper investigates the mechanisms for the generation of fiber path defects during processing of composites prepreg materials and proposes new predictive numerical models. A key focus of the work was on thick sections, where consolidation of the ply stack leads to out of plane ply movement. This deformation can either directly lead to fiber waviness or can cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 53 publications
(73 reference statements)
2
69
1
Order By: Relevance
“…Both Belnoue et al and Sjölander indicate that squeeze flow effects may appear when forming curved geometries. The squeeze flow observed in the fiber direction perpendicular to the forming direction was, in Ref.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Belnoue et al and Sjölander indicate that squeeze flow effects may appear when forming curved geometries. The squeeze flow observed in the fiber direction perpendicular to the forming direction was, in Ref.…”
Section: Methodsmentioning
confidence: 99%
“…Thermoset prepregs compaction limit is often reached at high temperature and pressure levels. Belnoue et al performed a study on compaction of uncured prepreg and used squeeze flow and resin bleed out flow as mechanisms in the modeling work. This experimental work showed the existence of flow transition mechanisms between squeezing and bleeding flows.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6,15]) were mainly concerned with prediction and experimental evaluation of the final shape of the specimen, especially corner parts, and were able to detect the effect of layup on the shape or the effect of processing conditions on thickness of flat laminates. The latest research [3,16,17] has shown that more advanced models can predict geometry of complex shape specimens.…”
Section: This Paper Employs the Hyper-viscoelastic Consolidation Modementioning
confidence: 99%
“…Additionally, Kugler and Moon [90] have shown the significant influence of the cooling rate and length. The prediction of instabilities originating from the differences in CTE is very complex, as shown in the studies of Dodwell et al [18] and Belnoue et al [91].…”
Section: Cte Mismatchmentioning
confidence: 99%
“…The strength reductions are associated with out of plane stresses and resulting delamination emanating from the cut ply ends and the small resin-rich zones at the ends of the terminated plies. Belnoue et al [91] investigated the wrinkle formation in tapered laminates under double-sided rigid tooling due to variabilities in the ply thickness, which would lead to a mismatch between mold and preform. The thickness variation of the laminate upon consolidation is responsible for the generation of excess length.…”
Section: Ply Drops In Tapered Laminatesmentioning
confidence: 99%